Synthesis and properties of aromatic 1,3-diketones and bis-(1,3-diketones) obtained from acetophenone and phtalic acids esters - Zawadiak, Jan; Mrzyczek, Marek; Piotrowski, Tomasz (European Journal of Chemistry, 2011)
Dibenzoylmethane and six aromatic 1,3-diketones containing a dibenzoylmethane moiety were synthesized from acetophenone and the appropriate ester in crossed-Claisen condensations. The synthesized diketones include derivatives containing carboxyl and ester groups; bis-(1,3-diketones) were also prepared. The absorption of UV radiation of the obtained compounds was investigated in various solvents, and their molar absorption coefficients were calculated. The ratio of tautomers and keto-enol equilibrium constants were calculated using 1H NMR techniques. Aromatic bis-(1,3-diketones) demonstrated strong hyperchromic effects. The keto-enol equilibrium of the investigated compounds is strongly shifted to the enol form, especially in non-polar solvents.